Evaluasi Penerapan Kesehatan Dan Keselamatan Kerja Di Bengkel Teknologi Mekanik Jurusan Teknik Mesin Politeknik Negeri Kupang Dengan Metode HIRADC - Desi Natalia Ratu; Amros A. Tuati; Oktavianus D. Rerung; Jonri Lomi Ga; Alexius L. johanis (Universitas Nusa Cendana, 2025)
HIRADC (identification, hazard analysis, and risk control) is the application of controls used to systematically review processes or operations in a system. This research using HIRADC method, summarized in the form of transcripts, analyzed using research forms and risk assessment matrices to identify the hazards levels present in the mechanical technology workshop/laboratory, measurements taken to prevent accidents. Based on the interview results, it was found one accident. The questionnaire results showed the majority of respondents had a positive perception of safety and service quality, Over 70% stating that it was safe and of good quality. However, the frequency of service use was relatively low, with over 50% of respondents stating they had never used the service. Identification and evaluation revealed 1 High Risk, 6 Moderate Risks, and 1 Low Risk. Based on these results, they were categorized as 75% physical and 25% chemical. In addition to the results of technical, administrative, and PPE controls, the steps presented in this study include control measures and preventive actions that can be implemented to improve OSH aspects in the laboratory. Thus, workshop/laboratory managers can develop strategies to reduce risks and enhance user safety.